Implementasi Strategi Bauran Pemasaran Dalam Upaya Menarik Minat Peserta Didik Baru Pada Sekolah Menengah Pertama Islam - Akhwan Mashudi Akhwan Mashudi; Bahtiar Bahtiar; Nurul Yakin (J-MPI (Jurnal Manajemen Pendidikan Islam), 2022)
The purpose of this study is to explain the application of the marketing mix strategy in an effort to attract the interest of new students at Islamic Junior High School (SMPI) Al-Mujahidin Tempos. This research is included in the qualitative research group, where the data collection techniques use observation, interviews, and documentation techniques. Data analysis consists of data presentation, data reduction, and then drawing conclusions. The results showed that SMPI Al-Mujahidin Tempos succeeded in increasing the interests and number of new students. The marketing mix strategies used include products (products), price (price), place (location), promotion (promotion), people (human resources), physical evidence (physical evidence), and process (process). The products offered are schools based on Islamic habits, including tahfizul qur'an, tahlilan, barzanji reading and, environmental preserving. Free school entrance fees are even given school uniforms. The main promotion activities through recitation conducted by the leaders of Islamic boarding schools, school principals and teachers, and the spread of brochures through social media and announcement banners in schools. Development of adequate learning supporting infrastructure facilities. While the learning process is carried out with the 13 -based Islamic culture curriculum.